The Urgency in Implementing the Accounting Sustainability of Spiritual Dimension in the Sustainability of Company - Utama, Yopi Yudha; Sukoharsono, Eko Ganis; Baridwan, Zaki (Universitas Negeri Malang, 2018)
The purpose of this paper is to understand the concept of accounting sustainability of spiritual dimension as a concept of sustainability. Sustainability accounting of spiritual dimension or can be called as Aksus is a sustainable concept which contains the spiritual dimension that complements the previous three dimensions (profit, people, and planet). This study uses the critical discourse analysis method of Norman Fairclough. The result is that there is a representation of Sukoharsono's thoughts in the text, as well as the relation to Sukoharsono's reader and identity for the readers that occur on the look of a text. Thought of concern for the survival of all beings is present in the text. At the level of discourse practice such as the production of texts, Sukoharsono does so with great caution and accordance with the sciences he has had, so it can be said if the production of the text is a manifestation of his perspective on accounting and sustainability. At the level of sociocultural practice, there is an influence of the current business situation and the social community that exists. The analysis shows Sukoharsono's commitment to the world of accounting and sustainability, and that business people always continue to care about the survival of all beings in addition to fulfilling their benefits